(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The study was designed to work on the determination of growth pattern of lesser spiny eel Macrognathus aculeatus (Bloch, 1786) evaluating length-length relationships. Lesser spiny eel is a small indigenous fish species collected monthly for a year from Dingaputa haor located at Mohanganj upazila of Netrokona district in Bangladesh. The standard length and total length of male ranged from 93 to 203 mm and from 101 to 214 mm, respectively. The standard length and total length of female ranged from 105 to 243 mm and from 108 to 256 mm respectively. The length-length relationship is described algebraically in the form of y = a + bx, and growth pattern was inferred to the direct proportionality between two lengths. The present study established the relationships between standard length and total length for male, female and combined fish separately. The constants of linear relationship of male in all months varied (slope, 1.01-1.07; intercept, -0.58-9.63). The generalized relationship of male was TL = 1.03 SL + 6.25. The constants of linear relationship of female in all months varied (slope, 0.99-1.05; intercept, 2.59-12.09). The generalized relationship of female was TL = 1.03 SL + 5.826. The constants of linear relationship of combined sex in all months varied (slope, 0.95-1.05; intercept, 2.41-18.78). The generalized relationship of combined sex was TL = 1.02 SL + 7.49. Correlation coefficents, r (≥ 0.913) and coefficients of determination, r2 (≥ 0.834) were high in all regression analyses in this study. Based upon r and r2, present study explained that standard length and total length were strongly associated, and standard length was very good predictor of total length. The growth pattern were isometric in September, November, December, February, March and April and allometric in October, January, May, June, July and August based on SL-TL relationship for male population. The growth pattern were isometric in October, March, April, July and August and allometric in November, December, January, February, May, June and September based on SL-TL for female population. The growth pattern were isometric in April, June and August and allometric in September, October, November, December, January, February, March, May and July based on SL-TL for combined population. This study would be beneficial for future research in order to make comparison between years and locations. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 471-482